Le palestre italiane nell'Ottocento: modelli regionali a confronto - Elia, Domenico Francesco Antonio (Studi sulla Formazione/Open Journal of Education, 2021)
The investigation involves a statistical analysis of educational gymnastics equipment in Italian schools during the 19th century. The purpose of the study is not only to survey the state of gyms in the 1880s but also to examine the extent to which they were equipped as prescribed by the School Regulation of 1878. The paper provides an accurate map of gymnastics education in Italy in the Liberal Age. Conversely, it seems necessary to focus on local developments, didactic approaches and institutions (Sani 2011).